Bixin, a performing natural antioxidant in active food packaging for the protection of oxidation sensitive food. (15th April 2023) - Stoll, Liana; Maillard, Marie-Noelle; Le Roux, Even; Hickmann Flôres, Simone; Nachtigall, Sonia Marli B.; Rios, Alessandro; Domenek, Sandra
Abstract: Natural antioxidants used in active packaging are an effective food technology to preserve oxygen sensitive foodstuff. Bixin, a carotenoid with coloring and antioxidant properties extracted from annatto seeds, was included in plasticized or not poly(lactide) (PLA) films using melt processing at 1 g/kg to increase the light barrier of the packaging and to deliver antioxidants to the food matrix. The melt processing caused degradation of bixin to more than 75%. The degradation products were analyzed using liquid chromatography coupled to mass spectrometry. The principal degradation process was cis/trans -isomerization. Despite this important structural change satisfactory barrier properties to UVA and UVB light were conserved in PLA films. Analysis of the protective performance of the packaging materials showed that the shelf-life of the vitamin riboflavin could be increased, and the augmentation of the peroxide values in sunflower oil slowed down. Bixin is therefore a very promising natural antioxidant, which could be used in packaging materials requiring melt processing. Highlights: Active packaging with bixin increases shelf-life of oxidation sensitive foods. Cis/trans isomerizing is main degradation route during melt processing of packaging. Isomerized and partially degraded bixin stays effective in protecting food.